Modified Leadbetter-Politano Ureteroneocystostomy: A Safer Procedure - Ozdemir, Tunc; Sayan, Ali; Koyluoglu, Gokhan (Urology Journal, 2020)
Purpose: Open surgical reimplantation of ureters is a highly successful procedure, with reported correction rates of 95 to 99 percent regardless of the severity of vesicoureteral reflux (VUR). Leadbetter-Politano ureteroneocystostomy is one of the most preffered technique for open ureteroneocystostomy. The authors report the modified Politano-Leadbetter technique with extravesical mobilization and transection of the ureter at the level of ureterovesical junction and intravesical reimplantation. Materials and Methods: Fifty-seven children with unilateral VUR, underwent modified Leadbetter-Politano ureteral reimplantation with extravesical mobilization and transection of the ureter at the level of ureterovesical junction and intravesical reimplantation. Persistence of VUR despite endoscopic correction, breakthrough infections, complications due to antibiotics, progressive renal scarring, reflux nephropathy, and parental preference were indications for open reimplantation. Operations were done by two full-time pediatric surgeons. Operation time and hospital stay of the patients, reflux persistency, voiding dysfunction and complications were recorded. Results: No ipsilateral VUR was detected postoperatively. Mean operation time was 76.54 min (±8.76 min; range, 70-86 min) Mean duration of the hospital stay is 82.31 h (±9.78 h; range, 71-93 h). Postoperative gross hematuria was not seen in any patients. No voiding dysfunction and no late complications was encountered. Conclusions: Modified Leadbetter-Politano technique is a good option to treat VUR with success rate up to 100% without any major complicatons such as viscus perforation and ureteral obstruction. It is a rather simple technique that require less operative time.